2018
DOI: 10.25034/ijcua.2018.3668
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Social Interactions in Market Square and Its Impact on Community Well-Being

Abstract: A B S T R A C T

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Proactive spatial interventions of environmental factors in residential areas can improve residents' health. [54][55][56][57][58][59][60][61][62][63][64] However, research on the impact of built environment quality elements on the subjective well-being of older people after the quality of the neighborhood environment in settlements has been improved is lacking. The study examines the current practice of multi-quality renewal in existing Dalian neighborhoods, examining the differences in the impact of multi-quality elements on the subjective well-being of the older adults in different neighborhood environment types, and observing the degree of change in the subjective well-being of the older adults from the standpoint of psychological resilience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proactive spatial interventions of environmental factors in residential areas can improve residents' health. [54][55][56][57][58][59][60][61][62][63][64] However, research on the impact of built environment quality elements on the subjective well-being of older people after the quality of the neighborhood environment in settlements has been improved is lacking. The study examines the current practice of multi-quality renewal in existing Dalian neighborhoods, examining the differences in the impact of multi-quality elements on the subjective well-being of the older adults in different neighborhood environment types, and observing the degree of change in the subjective well-being of the older adults from the standpoint of psychological resilience.…”
Section: Discussionmentioning
confidence: 99%
“…31 As a result, mental activity and emotional affect are often used as a manifestation or moderator of well-being, as well as ways to express well-being. 53 Some studies have also found a strong link between the residential environment, housing, and health, [54][55][56][57][58][59][60][61][62][63][64] and Li Shuran and Chen Changhui argue that paying attention to the special needs of the older adults for their living environment is beneficial to their physical and mental health; 54 Zhang and Lin et al proactive spatial interventions in residential environmental factors can have a positive impact on residents' health and promote China's health. 55 Currently, there has been little research on the impact of built environment quality elements on the subjective wellbeing of older people following environmental quality improvements (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies comparatively measure the quality of squares and public open spaces with the indexes created by mathematical expression of the variables obtained using survey and observation techniques (Mehta, 2014;Terzi et al, 2019;Praliya & Garg, 2019). The study on market squares, which is a public space that reflects intense human interaction, has revealed that there is a connection between the built environment, human relations and well-being (Agboola et al, 2018).…”
Section: Literature Review On Spatial Configuration and Spatial Quality Of Public Spacesmentioning
confidence: 99%
“…In each city, constraints and opportunities should be wholly addressed to reflect peculiar urban systems of environmental, social and economic life [22]. It has been observed that the system of transportation impacts the liveability of contemporary cities in real-life situations [23] and that social integration [24] and resource management enhances resilience and durability in cities [25]. In point of fact, the interactions between dwellers, infrastructure and transport networks are the undergirding of the micro-structure of sustainable cities [26].…”
Section: Approaches To Aesthetic Urban Planningmentioning
confidence: 99%